Senior medical students’ awareness of radiation risks from common diagnostic imaging examinations - Scali, Elena; Mayo, John; Nicolaou, Savvas; Kozoriz, Michael; Chang, Silvia (Canadian Medical Education Journal, 2017)
Background: Senior medical students represent future physicians who commonly refer patients for diagnostic imaging studies that may involve ionizing radiation. The radiology curriculum at the University of British Columbia provides students with broad-based knowledge about common imaging examinations. The purpose of this study was to investigate students’ awareness of radiation exposures and risks. Methods: An anonymous multiple-choice cross-sectional questionnaire was distributed to final year medical students to assess knowledge of radiation from common diagnostic examinations and radiation-related risks following completion of the longitudinal radiology curriculum, carried out over the four years of medical training. Results: Sixty-three of 192 eligible students participated (33% response rate). The majority felt that knowledge of radiation doses of common imaging examinations is somewhat or very important; however, only 12% (N = 8) routinely discuss radiation-related risks with patients. While all respondents recognized children as most sensitive to the effects of radiation, only 24% (N = 15) correctly identified gonads as the most radiation-sensitive tissue. Almost all respondents recognized ultrasound and MRI as radiation free modalities. Respondents who correctly identified the relative dose of common imaging examinations in chest x-ray equivalents varied from 3-77% (N = 2 – 49); the remaining responses were largely underestimates. Finally, 44% (N = 28) correctly identified the excess risk of a fatal cancer from an abdominal CT in an adult, while the remainder underestimated this risk. Conclusion: Medical students acknowledge the importance of radiation-related issues to patient care. While almost all students are familiar with radiation-free modalities, many are not familiar with, and commonly underestimate, the relative doses and risks of common imaging studies. This may expose patients to increasing imaging investigations and exposure to radiation hazards.